216k views
3 votes
Solve x2 - 16x + 60 = -12 by completing the steps. First, subtract 60 from each side of the equation. Next, add to each side of the equation to complete the square.

1 Answer

0 votes

Answer:

The answer is NO SOLUTION

Explanation:

Firstly, we have to subtract 60 from each side of the equation:


x^2-16*x+60=-12\\x^2-16*x+60-60=-12-60\\x^2-16*x=-72

Then, to complete a square of a binomial, the rules are:

Let
(a+b)^2 a square of a binomial, its expansion is:

  1. square of the first term
    a^2
  2. twice the product of the two terms
    2*a*b
  3. square of the last term
    b^2

So,
(a+b)^2=a^2+2*a*b+b^2

Then , we have the first term that is
x and the second term is
-8 because
2*(x)*(-8)=-16*x.

Therefore, we need to add 64 (=
(-8)^2) from each side of the equation:


x^2-16*x+64=-72+64\\(x-8)^2=-8\\√((x-8)^2)=√(-8)\\x-8=√(-8)

Finally, we know that it doesn't exist negative square root in the real number group, so there are not "x" values ​​to solve the equation.

User Adriano Monecchi
by
6.3k points